PERLINDUNGAN HUKUM KONSUMEN KARTU FLAZZ YANG DITERBITKAN OLEH BANK BCA - Fauzan Ramadhan; Elfrida Ratnawati (LPPM Universitas Ekasakti Padang, 2023)
Technological developments have brought changes to payments in the form of cash in conventional metal and paper forms, which have now developed in the form of electronic payment instruments. The use of non-cash payment electronic money (FLAZZ) besides being able to facilitate transactions can also cause losses to the owner if the FLAZZ is lost or stolen. Transactions using e-money can be carried out without going through an authorization process such as a PIN (Personal Identification Number) so that e-money can be used easily by unauthorized persons. Bank Indonesia Regulation Number 20/6/PBI/2018 contains regulations related to financial compensation but are not clear and detailed, so these unclear regulations lead to different interpretations between institutions. The purpose of this paper is to find out the legal arrangements for electronic money owners in the event of a loss on an e-money card and to find out the responsibility of the bank as a provider of non-cash payment instruments for losses suffered by e-money. - the owner of the money card. The research method used in this paper is normative legal research method. Studies show that electronic money compensation can only be made if there is damage from the issuer. The bank is not responsible for losses to e-money owners due to user negligence that violates consumer protection principles. Banks as issuers of electronic money are not responsible for losses to FLAZZ owners where this rule violates the principle of consumer protection.